The Meaning of Social Media as a Communication and Promotion Tool by MSMES with a Phenomenological Approach - Sandy Gunarso Wijoyo; Nurali Nurali; Agus Paryadi; Rina Sunartyas Ramdhani (Universitas KH. Abdul Chalim Mojokerto, 2026)
Digital transformation has changed the way micro, small, and medium enterprises (MSMEs) communicate and promote their products. Social media is not only a means of sharing information but also serves as a relatively inexpensive and effective interactive promotional tool. This study aims to understand the meaning of social media as a communication and promotional tool from the perspective of MSMEs in North Cikarang. The research method used is qualitative with a phenomenological approach. Data were obtained through in-depth interviews, participant observation, and documentation of eight MSMEs selected using purposive sampling. Data analysis was conducted thematically with an emphasis on interpreting the subjective experiences of informants. The results of the study indicate that MSMEs interpret social media in four main dimensions: (1) as a two-way communication tool that strengthens interactions with consumers, (2) as a product promotion showcase through visual content, short videos, and live selling, (3) as a business identity space that builds consumer image and trust, and (4) as a learning platform through digital trends and consumer feedback. The main obstacles faced include limited digital literacy, limited resources, and the dynamics of platform algorithms. Social commerce phenomena such as TikTok Shop are seen as opening up new market opportunities, although they also pose a risk of platform dependence. This study emphasizes the importance of increasing digital literacy, diversifying promotional strategies, and ecosystem support from the government and related institutions so that MSMEs are more adaptive to digital change. These findings provide theoretical contributions to the phenomenology-based digital marketing literature and practical implications for the sustainability of MSMEs in the era of a social media-based economy.